Influence of concentrations of chloride ions on electrochemical corrosion behavior of titanium-zirconium-molybdenum alloy - Hu, Ping; Song, Rui; Li, Xiao-jing; Deng, Jie; Chen, Zhen-yu; Li, Qin-wei; Wang, Kuai-she; Cao, Wei-cheng; Liu, Dong-xin; Yu, Hai-liang (Journal of alloys and compounds, 2017)
Titanium-zirconium-molybdenum (TZM) alloy was fabricated by using powder metallurgy and rolling techniques. Electrochemical corrosion behavior of the alloy was studied quantitatively using potentiodynamic polarization and scanning electron microscope. Effect of different chloride ions concentrations on corrosion resistance and electrochemical corrosion mechanism on TZM alloy was investigated. Results show that pitting corrosion and intergranular corrosion of TZM alloy mainly occurs in sodium chloride solution. Corrosion generates firstly in the form of pitting corrosion around second phase particles and increases with corrosive media Cl− concentration increasing, and then the intergranular corrosion occurs along grain boundaries and defects. Cl− corrosion can effectively destroy the passive film formed on the sample surface. As the Cl− concentration of corrosive media increases, the corrosion rate of TZM alloy increases until 1.0 mol/L and then decreases. TZM alloy exhibits good corrosion resistance when the concentration of Cl− in corrosive media is 0.5 mol/L or 1.5 mol/L. •The TZM alloy corrosion rates in different concentrations Cl− have been tested.•Described corrosion mechanism of TZM alloy in different concentrations Cl−.•Provided a theoretical basis to improve the corrosion resistance of TZM alloy.